2017
DOI: 10.1016/j.jchf.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnic Differences in Outcomes Among Hospitalized Medicare Patients With Heart Failure and Preserved Ejection Fraction

Abstract: OBJECTIVES This study analyzed HFpEF patient characteristics and clinical outcomes according to race/ethnicity and adjusted for patient and hospital characteristics along with socioeconomic status (SES). BACKGROUND The proportion of hospitalizations for heart failure with preserved ejection fraction (HFpEF) has increased over the last decade. Whether the short- and long-term outcomes differ between racial/ethnic groups is not well described. METHODS The Get With The Guidelines–Heart Failure registry was li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 26 publications
0
32
0
2
Order By: Relevance
“…56 In patients with HFpEF, specifically, black patients were found to have higher readmission rates compared with white patients, and no difference was found in readmission rates for Hispanic and Asian patients compared with white patients. 57 The cohort size for Hispanic and Asian patients in these studies is much smaller and may have limited the statistical power to detect a difference in readmission rates. Several studies have reported that black and Hispanic patients hospitalized for HF tend to have lower 30-day and 1-year mortality rates, 56,58 and the etiology of these differences remains unclear.…”
Section: Demographic Characteristicsmentioning
confidence: 98%
“…56 In patients with HFpEF, specifically, black patients were found to have higher readmission rates compared with white patients, and no difference was found in readmission rates for Hispanic and Asian patients compared with white patients. 57 The cohort size for Hispanic and Asian patients in these studies is much smaller and may have limited the statistical power to detect a difference in readmission rates. Several studies have reported that black and Hispanic patients hospitalized for HF tend to have lower 30-day and 1-year mortality rates, 56,58 and the etiology of these differences remains unclear.…”
Section: Demographic Characteristicsmentioning
confidence: 98%
“…Studies have shown that ethnicity plays a role in disease progression and severity [24][25][26]. A large cohort study investigating 53,065 heart failure patients showed that one-year mortality was lower in Black, Hispanic and Asian patients compared to White patients [27] and a meta-analysis has shown that Indian and Malay ethnic groups in South East Asian countries are at higher risk to develop metabolic diseases like diabetes [28][29][30]. A propensity-matched study For every 1g/dL drop in haemoglobin done amongst coronary artery bypass graft patients showed that South Asian ethnicity had a survival benefit compared its predominantly White counterparts [31].…”
Section: Ethnicitymentioning
confidence: 99%
“…9 Our finding of lower readmission risk for black patients is in contrast to findings from the general population, in which black, compared with white, race has been associated with increased risk of readmission both generally 10 and following a heart failure hospitalization. 13,14 Reasons for this are uncertain but may relate to the controversially termed phenomenon known as reverse epidemiology, 15 in which nonwhite adult patients receiving dialysis have generally more favorable outcomes than white adult patients. Further examination should be undertaken and findings leveraged to improve the care of patients of all races.…”
Section: Discussionmentioning
confidence: 99%